MMS Observation of Magnetic Reconnection in the Turbulent Magnetosheath. Issue 11 (26th November 2017) - Vörös, Z.; Yordanova, E.; Varsani, A.; Genestreti, K. J.; Khotyaintsev, Yu. V.; Li, W.; Graham, D. B.; Norgren, C.; Nakamura, R.; Narita, Y.; Plaschke, F.; Magnes, W.; et al.
Abstract: In this paper we use the full armament of the MMS (Magnetospheric Multiscale) spacecraft to study magnetic reconnection in the turbulent magnetosheath downstream of a quasi‐parallel bow shock. Contrarily to the magnetopause and magnetotail cases, only a few observations of reconnection in the magnetosheath have been reported. The case study in this paper presents, for the first time, both fluid‐scale and kinetic‐scale signatures of an ongoing reconnection in the turbulent magnetosheath. The spacecraft are crossing the reconnection inflow and outflow regions and the ion diffusion region (IDR). Inside the reconnection outflows D shape ion distributions are observed. Inside the IDR mixing of ion populations, crescent‐like velocity distributions and ion accelerations are observed. One of the spacecraft skims the outer region of the electron diffusion region, where parallel electric fields, energy dissipation/conversion, electron pressure tensor agyrotropy, electron temperature anisotropy, and electron accelerations are observed. Some of the difficulties of the observations of magnetic reconnection in turbulent plasma are also outlined. Key Points: Magnetic reconnection is observed in the magnetosheath Reconnection is observed in turbulent environment Fluid and kinetic signatures of magnetic reconnection are observed for the first time in the magnetosheath